Carbon dot‐based fluorescent probes for sensitive and selective detection of luteolin through the inner filter effect. (16th October 2018) - Sun, Qianqian; Long, Yuwei; Pan, Shuang; Liu, Hui; Yang, Jidong; Hu, Xiaoli
Abstract: As a flavonoid, luteolin (LTL) has been universally studied due to its many advantages. Luteolin is a component in drugs and accurate detection is important to determine their LTL content and estimate their disposal effects. In our study, we found that the strong fluorescence of CDs made using ammonium citrate with the quantum yield (QY) of 8.8%, could be quenched sharply by LTL through the inner filter effect (IFE), and therefore a fluorescence assay for LTL detection using CDs as probes was devised. In this fluorescence assay, the limit of detection (LOD) was 0.07 μmol L −1 with a dynamic range of 0.23–50.0 μmol L −1 . The CDs also possessed excellent selectivity and achieved acceptable recovery and relative standard deviation (RSD). Importantly, for use of environmentally friendly and nontoxic CDs as fluorescent probes to detect LTL, its operation, instruments and materials are cheap and easy. Therefore, this study improved the ease of LTL detection, and can be used widely.